pengaruh sifat optik terhadap sifat optik nanokomposit Fe3O4/ZnO/Graphene Quantum Dots (GQDs) - Sintha Widiawati; Astuti Astuti (Jurusan Fisika FMIPA Universitas Andalas, 2024)
This study aims to investigate the impact of isopropanol on the optical properties of the Fe₃O₄/ZnO/GQDs nanocomposite. The synthesis of Fe₃O₄ and ZnO nanoparticles was conducted using the coprecipitation method, followed by the synthesis of GQDs using the hydrothermal method with varying concentrations of isopropanol. Subsequently, the Fe₃O₄/ZnO nanocomposite was combined with GQDs synthesized using the sonication method. The amalgamation of magnetic and luminescent materials holds promise for applications in the biomedical field, particularly in bioimaging. XRD data analysis revealed crystal structure alterations attributed to the incorporation of carbon elements in both ZnO and Fe₃O₄. The TEM results indicated a particle size of 16.2 nm for the Fe₃O₄/ZnO/GQDs nanocomposite with a 10 ml isopropanol variation. Identified phases from the XRD analysis include Fe₃O₄, ZnO, and GQDs. UV-Vis spectroscopy detected distinctive absorbance peaks at wavelengths of 323.7 nm, 333.0 nm, 329.9 nm, and 323.9 nm. Moreover, the energy gap exhibited an increase with escalating concentrations of isopropanol in the GQDs. Photoluminescence analysis yielded robust, broad emission bands characterized by orange and red luminescence.